A-110 Translational research to advance the prevention and treatment of HIV-associated Malignancies. (January 2016) - Casper, Corey
Abstract : Cancer has emerged as a leading cause of morbidity and mortality among HIV-infected persons worldwide. The incidence of cancer is increased exponentially in HIV-positive individuals, and in the United States it is estimated that nearly 10% of persons living with HIV will develop cancer in their lifetime. Coupled with evolving data which find that persons with HIV who develop cancer have a significantly reduced odds of surviving their cancer, new strategies for cancer prevention and treatment in persons living with HIV are needed. Over the past decade, we have conducted research in HIV-associated malignancies in Seattle and in partnership with the Uganda Cancer Institute in Kampala. In this presentation, data will be discussed from several types of studies: prospective cohort studies to define the natural history of infection with oncogenic viruses in HIV-infected individuals, studies examining the genomics of HIV-associated tumors, epidemiologic investigations of the relationship between HIV and cancer in low-resource settings, translational studies of virus and tumor immunology, and clinical trials of agents for HIV-associated cancer treatment and prevention. Finally, thoughts on how translational research can reduce the burden of HIV-associated cancers in both low- and high- resource settings will be offered.